2020
DOI: 10.1111/jace.17185
|View full text |Cite
|
Sign up to set email alerts
|

High‐pressure behavior and phase stability of Na2B4O6(OH)2·3H2O (kernite)

Abstract: The high-pressure behavior of kernite [ideally Na2B4O6(OH)2•3H2O, a ~7.02 Å, b ~9.16 Å, c ~15.68 Å, β = 108.9°, Sp. Gr. P21/c, at ambient conditions], an important B-bearing raw material (with B2O3  51 wt%) and a potential B-rich aggregate in radiation shielding materials, has been studied by single-crystal synchrotron X-ray diffraction up to 14.6 GPa. Kernite undergoes an iso-symmetric phase transition at 1.6-2.0 GPa (to kernite-II). Between 6.6-7.5 GPa, kernite undergoes a second phase transition, possibly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
(32 reference statements)
1
3
0
Order By: Relevance
“…The deformation mechanisms above described for meyerhofferite have already been observed in other hydrated borates: e.g. in the kernite-to-kernite-II phase transition, where the coordination number of the cation site Na1 increases from VI to VII with similar mechanisms (Comboni et al, 2020b). In detail, one oxygen site leaves the coordination sphere of Na1 and is replaced by another one, which is pushed towards Na1 by the tilting of the BO x units.…”
Section: High-pressure Phase Transitions In Hydrated Boratessupporting
confidence: 52%
See 3 more Smart Citations
“…The deformation mechanisms above described for meyerhofferite have already been observed in other hydrated borates: e.g. in the kernite-to-kernite-II phase transition, where the coordination number of the cation site Na1 increases from VI to VII with similar mechanisms (Comboni et al, 2020b). In detail, one oxygen site leaves the coordination sphere of Na1 and is replaced by another one, which is pushed towards Na1 by the tilting of the BO x units.…”
Section: High-pressure Phase Transitions In Hydrated Boratessupporting
confidence: 52%
“…In the previous study by Comboni et al (2020a), a sort of transient behaviour, detected also in other borates experiencing P-induced phase transitions with a relevant change in volume (e.g. kernite; Comboni et al, 2020b), was observed. In order to avoid this phenomenon, which could potentially be the sign of an incomplete re-equilibration of the crystal structure, for all the measurements preceding and following the phase transition, an average equilibration time of 1.5 h was applied.…”
Section: Methodsmentioning
confidence: 59%
See 2 more Smart Citations
“…In both the experiments, crystals did not recover after the phase transition. This was the most destructive phase transition observed in hydrated borates to date (e.g., Comboni et al, 2020bComboni et al, , 2022b, since the number of observed reflections was barely enough to properly index the diffraction pattern of the high-pressure polymorph, inderborite-II, which was found to be metrically monoclinic. The space group has not unambiguously determined.…”
Section: Discussionmentioning
confidence: 99%